PENERAPAN LEAN MANUFACTURE : UNTUK MEREDUKSI WASTE DI KONVEKSI XYZ - Fini Zanuar Utami (2021)
XYZ Convection is one of the apparel manufacturing companies located in Pengadegan, Purbalingga. In the production process in the company, some waste is still found. The problems faced by waste companies are defects, waiting, unnecessary movements, transportation, unnecessary inventory, overproduction and inappropriate processes, besides the separation of the sewing area 2 which is ±4km away, making transportation activities more and more. To reduce the waste that occurs, a lean manufacturing approach is used, the research begins with the Value Stream Mapping (VSM) method for mapping the production flow and information flow of a product. Then, the wastage was weighed using a questionnaire. Then the weighting is analyzed using VALSAT to determine what tools will be used next. To analyze the wastage factor, a fishbone diagram is used. In addition, it also provides a production layout proposal to reduce the distance of movement using the Systematic Layout Planning (SLP) method and a proposed finished goods storage shelf using the First In First Out concept. The results showed that the biggest waste was transportation waste with an average score of 1.31. The proposed improvements can save 20 seconds of value added time, 284 seconds of necessary but non-value added and 157 seconds of non-value added and a reduced displacement distance of 9.5m.